Handling and loading market-ready turkeys – Focus groups exploring the perspectives of live haul crew workers in the turkey industry - Luz A. Hernandez; Victoria R. Merenda; Monique D. Pairis-Garcia; Maria Coady; Alejandro Amaya; Jesse L. Grimes; Allison N. Pullin (Journal of Applied Poultry Research)
Summary: Improper handling and loading of market-ready turkeys during live haul presents significant challenges in the U.S. turkey industry. Bird injuries, such as bruises, scratches, and/or fractured or broken bones compromise animal welfare and lead to economic losses. However, the factors contributing to these handling challenges remain understudied. We aimed to identify barriers to implementing proper handling and loading techniques for market-ready turkeys through focus groups with commercial live haul crews. Participants identified three key themes: animal, farm, and human factors. Animal factors, such as bird sex, age, weight, and mobility, required crew members to modify handling strategies and varied the efficiency of live haul. The farm factors centered on the importance of preparing the barn environment for live haul. Adjusting lighting, ensuring good litter quality, scheduling nighttime shifts, using loading equipment correctly, and maintaining stable temperatures improve bird movement. Human factors included employee training methods, where informal training was the primary way in which crew members learned how to perform their tasks; the physical demands of the job, especially in challenging situations; and specific handling strategies to efficiently move birds and minimize injuries to animals and crew members. Animal, farm, and human factors are often interconnected, which compounds the complexity of ensuring proper animal handling for live haul. Future research in formal training, the design of farms, loading equipment, and personal protective equipment may mitigate the effects of these factors. Additionally, proactive teamwork and communication amongst veterinarians, producers, and live haul crews would better prepare farms for live haul.